LIFE CYCLE ASSESSMENT OF SUGAR AT CANE SUGAR INDUSTRY - Mohamad Yani, Ikawati Purwaningsih dan Mas Nandang Munandar (E-jurnal Agro-Industri Indonesia, 2012)
ABSTRACT National sugar industry holds an important role to meet the growing demand for sugar. Along with economic growth and technological progress, the activities of sugar production can cause an impact on the environment. Identification life cycle of sugar production process involves the use of raw materials and energy are needed to determine the efficiency of production and then analyzed for the environmental impact. Based on inventory data from sugar plant, the productivity of sugar cane as raw material  was 787 tons of cane / hectare, but its realization was only 690 tons of cane / hectare or 87.67% of the target. The use of energy in the steam plant from bagasse combustion, the energy generated by bagasse  of 2.83 x 1011 kcal, but the realization of 1.94 x 1011 kcal or 68.55% of the target. It indicates that the efficiency of steam decreased. Losses generated at sugar plant was 11,734.6 tons, this resulted in increased losses of waste and environmental impact. Liquid waste at sugar plant exceeds the quality standard that has been established, it is associated with efficiency in production processes that less optimal. Based on the inventory analysis showed that efficiency in the use of raw materials and energy are influenced by the life cycle starting from the gardens until sugar processing in the factory which will have implications on the environmental impact.   Keywords : life cycle assessment, sugar production process, energy efficiency, environmental  impact